Choose the answer based on the most efficient method as presented in the lesson.
Ir the first step in the solution of the equation 2x - 8 = 5x + 3 is "subtract 2x," then what should the next step be?
subtract 5x
add 8
subtract 3

Respuesta :

The next step is to subtract three making it -11 You have already combined your coefficients so your equations is -11=3x

Answer:

We will subtract 3 from both sides.

Step-by-step explanation:

The first step in the solution of the equation [tex]2x-8= 5x+ 3[/tex] is "subtract 2x,"

[tex]2x-8-2x= 5x+ 3-2x[/tex]

=> [tex]-8= 3x+ 3[/tex]

Now the next step will be subtract 3 from both sides.

[tex]-8-3= 3x+ 3-3[/tex]

=> [tex]-11= 3x[/tex]

And x = -11/3

ACCESS MORE